Do Aerial Nitrogen Depositions Affect Fungal and Bacterial Communities of Oak Leaves? - Borruso, Luigimaria; Bani, Alessia; Pioli, Silvia; Ventura, Maurizio; Panzacchi, Pietro; Antonielli, Livio; Giammarchi, Francesco; Polo, Andrea; Tonon, Giustino; Brusetti, Lorenzo (Frontiers in Microbiology, 2021)
The amount of nitrogen (N) deposition onto forests has globally increased and is expected to double by 2050, mostly because of fertilizer production and fossil fuel burning. Several studies have already investigated the effects of N depositions in forest soils, highlighting negative consequences on plant biodiversity and the associated biota. Nevertheless, the impact of N aerial inputs deposited directly on the tree canopy is still unexplored. This study aimed to investigate the influence of increased N deposition on the leaf-associated fungal and bacterial communities in a temperate forest dominated by Sessile oak (Quercus petraea (Matt.) Liebl.). The study area was located in the Mon-ticolo forest (South Tyrol, Italy), where an ecosystem experiment simulating an increased N deposition has been established. The results highlighted that N deposition affected the fungal beta-diversity and bacterial alpha-diversity without affecting leaf total N and C contents. We found several indicator genera of both fertilized and natural conditions within bacteria and fungi, suggesting a highly specific response to altered N inputs. Moreover, we found an increase of symbiotrophic fungi in N-treated, samples which are commonly represented by lichen-forming mycobionts. Overall, our results indicated that N-deposition, by increasing the level of bioavailable nutrients in leaves, could directly influence the bacterial and fungal community diversity.